Open-shell localized Hartree-Fock approach for an efficient effective exact-exchange Kohn-Sham treatment of open-shell atoms and molecules - Della Sala, Fabio; Görling, Andreas (Journal of Chemical Physics, 2003)
A generalization of the LHF method to open-shell systems is presented. In particular, an LHF approach denoted as open-shell LHF (OSLHF) method, is introduced within the symmetrized KS formalism. This method can be implemented within the framework of standard quantum chemistry codes and enables an efficient calculation of molecules with an odd electron number or, generally, with open-shells.